Age-specific trends in intravenous thrombolysis and mechanical thrombectomy utilization in acute ischemic stroke in children under age 18. Issue 4 (April 2023) - Kaur, Navreet; Patel, Smit; Ayanbadejo, Michael Omoniyi; Hoffman, Haydn; Akano, Emmanuel; Anikpezie, Nnabuchi; Aneni, Ehimen; Lamikanra, Oluwatomi; Wee, Claribel; Albright, Karen; Khandelwal, Priyank; Latorre, Julius Gene; et al.
Objectives: To evaluate current trends in the utilization of intravenous thrombolysis (IV-tPA) and mechanical thrombectomy (MT) in acute ischemic stroke (AIS) in various age groups of children in the United States. Methods: We conducted a serial cross-sectional study using primary AIS admissions in children ⩽ 17 years (weighted n = 2807) contained in the 2009–2019 KIDS Inpatient Database. Age-specific utilization frequency of IV-tPA and MT were calculated. Multivariable-adjusted models were used to evaluate demographic predictors of treatment. Results: From 2009 to 2019, there were 2807 AIS admissions in children in the KID of which 55.9% were in boys and 29.9% were 15–17 years old.128 (4.6%) received IV-tPA. IV-tPA utilization differed by age (5–9 years: 3.1%, 15–17 years 8.1% p value < 0.001). Overall MT usage was 2.3% and this also varied by age (1–4 years: 0.9% and 15–17years 4.0%, p value = 0.006). IV-tPA utilization almost tripled across the study period (2.5% 2009 to 6.5% in 2019, p value = 0.001) while MT use more than doubled over time (1.2% in 2009 and 3.0% in 2019, p value = 0.048). Increased IV-tPA utilization was seen primarily in children 10–14 years (0.8% in 2009 to 7.2% 2019, p value = 0.005) and 15–17 years (5.4% in 2009 to 10.4% in 2019, p value = 0.045). Utilization in younger age groups remained unchanged over time. MT usage was very variable across various age groups over time. IV-tPA and MT utilization increased over time in nonchildren's hospitals (both p values < 0.05) but usage in designated children's hospitals did not change significantly over time. In multivariable models, there was no significant difference in odds of IV-tPA and MT use by sex, race or insurance status. Conclusion: IV-tPA and MT utilization in pediatric AIS increased in the United States over the past decade mainly in older children 10–17 years. Utilization increased mainly in patients hospitalized in nonchildren's hospitals. Usage in children's hospitals did not change significantly over time.